Is There a Divergence Between Objective Measures and Subjective Perceptions of Poverty Trends? Evidence from West and Central Africa - Wodon, Quentin (World Bank, Washington, DC, 2012)
Several sub-Saharan African countries have succeeded at increasing their economic growth rate in recent years, and this has translated into substantial poverty reduction according to objective measures based on household survey data. At the same time, many people do not feel that the poverty situation has been improving in their country or community, and this is a source of concern for elected policymakers. To what extent is there a divergence between objective measures and subjective perceptions of poverty trends, and what may explain this divergence: the objective of this note is to document and discuss this issue using data from West and Central Africa and results from a series of poverty assessments recently completed at the World Bank.